High prevalence of mental disorders: a population-based cross-sectional study in the city of Ilam, Iran - Kakaei, Hojatollah; Maleki, Farajolah; Biderafsh, Azam; Valizadeh, Reza; Mansournia, Mohammad Ali; Pakzad, Iraj; Pakzad, Reza (Frontiers in Psychiatry, 2023)
Aim To determine the age- and sex-standardized prevalence and risk factors of depression, anxiety, and stress symptoms in the city of Ilam. Method In this population-based cross-sectional study, 1,350 people were invited using a multi-stage stratified cluster random sampling method. Depression, anxiety, and stress symptoms were measured using the DASS-21 standard questionnaire. For data analysis, multiple ordinal logistic regression was used in Stata version 12 software. A significance level of 5% was considered. Results The data of 1,431 people were analyzed. The age- and sex-standardized prevalence (95% CI) of severe depression, anxiety, and stress symptoms was 19.90% (17.64 to 22.16), 25.95% (23.48 to 28.43), and 15.75% (13.69 to 17.81), respectively. There was a positive association among depression symptoms with female sex (OR: 1.52; p < 0.003), Kurdish ethnicity (OR: 2.15; p < 0.004), low educational level (OR: 1.37; p < 0.031), job losing history (OR: 1.64; p < 0.001), mental disorders history (OR: 2.17; p < 0.001), hopelessness for the future (OR: 5.38; p < 0.001), and history of other diseases (OR: 1.67; p < 0.001). There was a positive association among anxiety symptoms with female sex (OR: 1.72; p < 0.001), job losing history (OR: 1.53; p < 0.003), mental disorders history (OR: 2.11; p < 0.001), hopelessness to future (OR: 3.33; p < 0.001) and history of other diseases (OR: 1.97; p < 0.001). Hopelessness for the future and a history of other diseases were the most effective variables for anxiety symptoms and stress symptoms. Conclusion A significant proportion of Ilam’s urban population suffers from mental disorders. Increasing people’s awareness, establishing counseling centers, and improving infrastructure should be considered by mental health policymakers who work in the province.